2009
DOI: 10.1158/1535-7163.mct-08-1122
|View full text |Cite
|
Sign up to set email alerts
|

In vivo antitumor effect of a novel inhibitor of protein geranylgeranyltransferase-I

Abstract: Protein geranylgeranyltransferase-I (GGTase-I) catalyzes protein geranylgeranylation, which is critical for the function of proteins such as Rho, Rac, and Ral. We previously identified several small-molecule inhibitors of GGTase

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 25 publications
2
35
0
Order By: Relevance
“…14 Aside from their use as synthetic intermediates, some 2,5-disubstituted-3-pyrrolines themselves exhibit significant biological activity. 15 Recently, our laboratory synthesized a library of 2,5-disubstituted pyrroline-3-carboxylates through the phosphine-catalyzed [3 + 2] annulations of resin-bound allenoates and imines. Several of these compounds were identified as geranylgeranyltransferase type-I (GGTase-1) inhibitors (GGTIs) and one, P61A6, exhibits excellent antitumor effects when tested in mice.…”
Section: Discussionmentioning
confidence: 99%
“…14 Aside from their use as synthetic intermediates, some 2,5-disubstituted-3-pyrrolines themselves exhibit significant biological activity. 15 Recently, our laboratory synthesized a library of 2,5-disubstituted pyrroline-3-carboxylates through the phosphine-catalyzed [3 + 2] annulations of resin-bound allenoates and imines. Several of these compounds were identified as geranylgeranyltransferase type-I (GGTase-1) inhibitors (GGTIs) and one, P61A6, exhibits excellent antitumor effects when tested in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, studies have proved that Ras signaling is initiated by FTase and GGTase-I [31]. Many prenyltransferase inhibitors have been discovered and are even in clinical trials for the treatment of a wide variety of cancers [32][33][34][35][36][37]. In 2003, Sun et al reported that a GGTI, GGTI-2154, can not only inhibit the viability of breast tumors but can also induce the regression of the tumor cells [38].…”
Section: Involvement Of Ftase and Ggtase-i In Different Diseasesmentioning
confidence: 99%
“…Two representative compounds, P3-E5 and P5-H6, compete with the substrate protein rather than GGPP (IC 50 = 313 nM for P3-E5 and 466 nM for P5-H6). P61A6 was synthesized by coupling P5-H6 with an L-phenylalanamide that showed excellent antitumor effect in a human pancreatic cancer xenograft model [33]. In addition, P61A6 was also identified with efficacy to inhibit growth of non-small-cell lung cancer cells in mice [74].…”
Section: Ggtase-i Inhibitorsmentioning
confidence: 99%
“…That fi nding, together with the observation that GGTase-I defi ciency is lethal in budding yeast ( 13 ), led many to suspect that GGTase-I would be an essential protein in mammalian cells. However, more recent studies of GGTase-I inhibitors have found less toxicity ( 18,19 ), and genetic models of GGTase-I deficiency (with a conditional knockout allele for Pggt1b , which encodes the ␤ -subunit of GGTase-I) suggested that mammalian cells can survive in the absence of GGTase-I ( 20,21 ). For example, inactivating GGTase-I in mouse pneumocytes retarded the growth of lung tumors without toxicity to normal lung tissue ( 20 ).…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%